MODELING INFORMATION-RECEIVING SYSTEMS AND PROCESSES IN THE TAX CONTROL SYSTEM - Jamalova, G.B. (SCIENCE and SOCIETY, 2026)
This article studies the impact of the taxpayer's risk status and tax evasion on the final distribution based on the Markov process. A number of experiments were conducted to model networks and the process of information dissemination in them. A comparative analysis of the obtained results is presented.